The Correlation Between Vocabulary Mastery And Students’ Ability In Arranging Random Words Into Good Sentence of The 2014 / 2015 Ninth Year Students of SMP Negeri 2 Stabat. - Bangun, Sylvia Faska (Journal of Applied Linguistics, 2021)
The objective of the study is to find out correlation between vocabulary mastery and students’ ability in arranging random word into good sentence of the 2014/2015 ninth year students of SMP Negeri 2 Stabat.The population of the study was the 2014/ 2015 the ninth year students of SMP Negeri 2 Stabat, totaling about 199 students. It was taken 20% from 199 students. It is 40 of them randomly as the sample of the research.This research was conducted by applying the correlationaldesign. The reliability of the test is counted by using Pearson Product Moment formula. The instrument was used to collect the data were multiple choicetest consisting of 20 items and essay test consisting of 20 items. Then the writer checked and gave score for both tests. The scores then were displayed in tables. After the data had been collected and analyzed, the findings showed that the value of t observed that is 0.50 is higher than the value of the ttable. It means that the test substantially high.This finding proves the hypothesis that the vocabulary mastery significantly correlates to students’ ability in arranging random word into good sentence of the 2014/2015 ninth years students of SMP Negeri 2 Stabat. Key words : Correlational Research, Vocabulary Mastery and Arranging Random Words into Good Sentence